Oligomers of Hexa-peri-hexabenzocoronenes as “Super-oligophenylenes”: Synthesis, Electronic Properties, and Self-assembly - WU, Jishan; WATSON, Mark D.; TCHEBOTAREVA, Natalia; WANG, Zhaohui; MüLLEN, Klaus (Journal of organic chemistry, 2004)
Hexa-peri-hexabenzocoronene (HBC) is a remarkable polycyclic aromatic hydrocarbon and is often called "superbenzene" because of its similarity to benzene. In this article we present the facile synthesis of oligomers of HBC, up to trimers (3, 4, 5a-c) with different modes of connection. UV-vis and fluorescence spectroscopy studies reveal that the oligomers are electronically decoupled. This arises from the small atomic orbital coefficients of the bridge-head carbon atoms, the large torsion angle between the HBC units, and the large distance of interacting transition dipoles due to the size of the HBC chromophore. For comparison, a methylene-bridged HBC dimer 6, so-called "superfluorene", was prepared. The induced planarity improves pi-conjugation and suppresses the geometrical relaxation of the backbone upon electronic excitation, leading to a prominent 0-0 transition band in the fluorescence spectra. The self-assembly of the oligomers and of superfluorene 6 was studied by wide-angle X-ray diffraction (WAXD) in the bulk state, and ordered columnar stacking occurs in the HBC dimer 3, p-HBC trimer 4, and superfluorene 6. Measurements of shear-aligned samples show that, despite increasing aspects ratio by linear entrainment of disks, the anitropic element that is subject to alignment by shear is the supramolecular columns.